Native purification of protein and RNA-protein complexes using a novel affinity procedure. - Kroiss, M.; Brünger, K.M.; Wiesner, J.; Grimmler, M.; Sickmann, A.; Fischer, U. (Fly, 2009)
Genetic studies in invertebrate model organisms such as Drosophila melanogaster have been a fundament of cell and developmental biology for more than one century. It is mainly the lack of an efficient purification strategy which has hampered biochemical and proteomic analyses of gene products. We describe a novel affinity-tag, termed TagIt-epitope, specifically designed for affinity-purifications of multiprotein complexes from Drosophila. TagIt-fusion proteins can be efficiently purified using a monoclonal antibody and eluted under native conditions by competition with synthetic peptide encompassing the epitope. We demonstrate that this tag is suitable for the purification of proteinaceous assemblies such as the PRMT5-complex and RNA-protein complexes such as snoRNPs from Drosophila Schneider2 cells. Furthermore, we describe a novel approach by which this tag can be used to affinity-purify RNA-binding proteins from cell extracts. Therefore, the TagIt-technique or modifications thereof will be of great value in analyzing macromolecular complexes in Drosophila and also other invertebrates by biochemical means. In addition, RNA-peptide hybrid molecules may become a novel tool to purify RNA binding proteins.